Aspiration syndromes and associated lung injury: incidence, pathophysiology and management - Košutova, P; Mikolka, P (Physiological research, 2021)
Aspiration is a common condition affecting healthy or sick patients which could create an acute or chronic inflammatory reaction in the lungs. Aspiration syndromes could be categorized according to a content entering the respiratory system into bacterial aspiration pneumonia with the gastric or oropharyngeal bacteria entering, aspiration chemical pneumonitis with bacteria-freegastric acid aspiration, or aspiration of a foreign body which causes an acute pulmonary emergency. There are differences in the clinical presentation of volume-dependent aspirations (microaspiration and macroaspiration): the higher is the volume of aspiration, the greater is the injury to the patient and more serious are the health consequences (with 70 % mortality rate for hospitalized patients). Aspiration syndromes can affect both the airways and pulmonary parenchyma, leading to acute lung injury, increased hospitalization rate and worse outcomes in critically ill patients. Impaired alveolar-capillary permeability, oedema formation, neutrophilic inflammatory response and pulmonary surfactant inactivation lead to reduced lung compliance and loss of aerated lung tissue and give rise to hypoxemia and respiratory failure. This review discusses the effect of aspiration events on the pulmonary tissue. The main focus is to distinguish the differences between bacterial and chemical pneumonia, their clinical presentation and symptoms, risk factors of developing the changes, possibilities of diagnostics and management as well as prevention of aspirations. Because of a risk of serious lung damage after the aspiration, pathophysiology and processes leading to lung tissue injury are discussed in detail. Data sources represent a systematic literature search using relevant medical subject headings.
Keywords: syndrom; Acute Lung Injury; Lung; aspirační pneumonie; lidé; Syndrome; akutní poškození plic; incidence; Incidence; Humans; plíce; Pneumonia, Aspiration